The current diagnosis and clinical prognostic value of kidney dysfunction in patients with coronary heart disease - K S Shafranskaia; I S Bykova (Терапевтический архив, 2014)
The problem of kidney dysfunction and its impact on outcomes in different groups of cardiac patients continue to being widely used. Kidney dysfunction is associated with a number of traditional cardiovascular risk factors. The use of new biomarkers, cystatin C in particular, to identify kidney injury can contribute to the improvement of early prediction of a risk for renal failure (RF). Cystatin C satisfies many characteristics as an ideal biomarker that can assist in not only detecting the early forms of kidney injury, but also in assessing the risk of RF, the needs for renal replacement therapy, and the risk of death in intensive care unit patients in cardiac clinics. Kidney involvement in many diseases, including those that are not initially regarded as renal, necessitates the elaboration of uniform approaches to managing patients with identified chronic RF, especially to the early prevention and treatment of its complications, such as anemia, phosphorus-calcium metabolic disorders, which substantially worsen the prognosis of other diseases.